Numerical simulation of gel fuel gas-phase ignition by a local source of limited heat content - Glushkov D. O. Dmitry Olegovich; Kuznetsov G. V. Geny Vladimirovich; Strizhak P. A. Pavel Alexandrovich; Taburchinov R. I. Roman Iljich (2019, 2019)
Title screen